Scaling climate information services using the local group for meteorological assistance in Mali - Diarra, Afoussata; Dossou-Yovo, E. R (2024)
The increasing variability of climate in Mali poses significant challenges to the agricultural sector, particularly rice-based systems. To address these issues, the AICCRA project established local groups for meteorological assistance to scale climate information services (CIS) in 9 sites (Baguineda, Baraoueli, Dioila, Macina, Niono, San, Segou, Selingue and Sikasso) in Mali. These groups bridge the gap between meteorological data and farmers' needs by providing tailored, location-specific climate advisories in local languages. By leveraging community-based dissemination mechanisms, these groups have successfully reached 2,250 farmers, enabling 81% to make climate-informed decisions. This resulted in measurable benefits, including an 800 kg/ha yield increase and a $267/ha income increase for participating farmers. Additionally, the training of 90 technicians, including women, has enhanced the capacity for sustainable CIS delivery. These achievements underline the effectiveness of localized, participatory approaches in addressing climate-related challenges in agriculture.